Legal Protection of Child Victims of Prostitution and its Contribution to the Development of Child Protection Law in Indonesia - Tutuko, Bambang (SMART: Journal of Sharia, Traditon, and Modernity, 2024)
This article analyzes the implementation of legal protection for child victims of prostitution in Lampung Province and its contribution to the development of child protection law in Indonesia. The research aims to evaluate the alignment between child protection practices and the provisions of Islamic law and positive law, and to identify regulatory needs that support comprehensive protection for child victims of sexual violence. The theory used is the theory of mashlahah mursalah, which emphasizes general welfare. This study employs field research with a qualitative approach and inductive reasoning. Data were collected through interviews and documentation from the Women and Children's Protection Agency of Lampung Province. The findings indicate that the implementation of legal protection for child victims of sexual violence falls short of the expectations set by the constitution and legislation. There is a need for more stringent policies to ensure that victims receive legal protection and free access to necessary facilities. The conclusion of this research is that efforts to protect child victims of sexual violence require regulatory improvements to align with the mandate of the 1945 Constitution. The contribution of this study lies in the development of policy recommendations that can enhance legal protection for children in Indonesia and provide insights into the importance of synergy between Islamic law and positive law in protecting children's rights.